Students’ Perception on Use of The PC Game: “Big City Adventure Sydney Australia” At MAN 2 Bukittinggi English Club Extracurricular to Improve Vocabulary Mastery - de Naldi, Irvink Fachrul Pratama; Tiarina, Yuli (Universitas Negeri Padang, 2024)
This research aims to know the students’ perception on use of the PC game: “Big City Adventure Sydney Australia” at MAN 2 Bukittinggi English Club Extra-curricular to improve vocabulary mastery. Vocabulary is essential in a language. Since learning vocabulary is the main point for learning other skills in a language. There is no doubt that vocabulary mastery plays an important role in the four language skills. Students can master English vocabulary in various interesting ways. One way is to use games as an attractive learning tool. Students can play the “Big City Adventure Sydney Australia” game to improve vocabulary mastery when they take part in extracurricular activities, namely English Club. English Club is the place for students to improve their English ability outside of regular classes. There are several benefits to join English Club at the school. One of them, mastering vocabulary in interesting way by playing game. English Club students play “Big City Adventure Sydney Australia” game to help them for mastering vocabulary. Descriptive research with quantitative method was used to assess the data in this research. Total sampling was used by the researcher to choose the sample of this study. The sample consisted of 93 English Club students. The questionnaire was used as the research instrument of this study. The finding showed that the students had positive perception on PC game: “Big City Adventure Sydney Australia” to improve vocabulary mastery the English Club students. It was represented by the total mean of the questionnaire (3.25). The results of this research showed that “Big City Adventure Sydney Australia” game helps the English Club students to improve their vocabulary mastery in the school extracurricular.